Comparative feeding ecology of four syntopic Hypostomus species in a Brazilian southeastern river - Villares-Junior,G. A. (2016)
Abstract Though their broad distribution in most Brazilian rivers, scarce studies concerning ecological interactions on Hypostomus species are available. This study observes the diet, the trophic interactions and some morphological aspects of four syntopic species of Hypostomus. These fishes were studied at the superior part of the Corumbataí river, at São Paulo state, southeastern Brazil. Analyses focused feeding patterns, their amplitude and whether there happens some food items overlap among the species. Fish were caught using cast nets at some points of the river. Species were chosen according to their local abundance and, so there were four main species: H. albopunctatus, H. ancistroides, H. regani and H. strigaticeps. Nine food items were found: sediments, fungi, diatoms, green algae, Tecamoeba, vegetal debris and invertebrates. There were not significant differences for the feeding pattern among the four Hypostomus species. The feeding niche amplitude has been larger for H. albopunctatus influenced by a larger amount of vegetal debris and invertebrates. Elevated niche overlap was found to happen among the species and also for their trophic morphology. Results may suggest that there is a similar pattern in food taken between four species of Hypostomus analyzed since all consume similar environmental resources and have similar anatomical features. However, a different intake insect larvae and plant material in H. albopunctatus diet indicate differences in local and how this species may be exploring their food compared to the others.